Criteria and indicators for sustainability forest management: assessment and monitoring of genetic variation - Namkoong, G.; Boyle, T.J.B.; El-Kassaby, Y.A.; Palmberg-Lerche, C.; Eriksson, G.; Gregorius, H.R.; Joly, H.; Kremer, A.; Savolainen, O.; Wickneswari, R.; Young, A.; Zeh-Nlo, M.; et al. (Forest Resources Development Service, Forest Resource Division, 2002)
The paper contains proposals for genetic criteria and indicators wich can form part of a more general set of, economic, environmental and social criteria and indicators for the monitoring of forest sustainability at the scale of forest management units. It proposes one criterion for conservation of forest genetic resources and four indicators related to processes that maintain genetic diversity. For each indicator, sets of verifiers are suggested which differ in the biologically relevant features they measure, in their precision, and in technical facilities they require. Finally, the need for rapid assessment and precision under difficult conditions requires research and development of efficient direct surrogate measures of the genetic resource. We therefore include recommendations for short- and medium term research that would improve the scientific value, cost effectiveness, ease of use, and further development of genetic criteria and indicators.